Hubungan Pemahaman Bacaan dengan Kemampuan Menulis Siswa Sekolah Dasar - Haryanti, Sherra Dwy; Sukma, Elfia (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This study aimed to describe the relationship between the reading comprehension skills of students' writing Elementary School fifth grade cluster II sub-district of Tanjung Raya. The method used is a correlation study. The sample used in this study amounted to 57 students. Based on statistical calculations student reading comprehension medium category with an average of 15.58. Writing skills of students included in the category that is on average 64.66. The correlation between the reading comprehension skills of students' writing at 0.617 imply r xy> r table (0.617> 0.256) with interpretation included in the strong category. This means that there is a correlation between reading comprehension skills of students' writing Elementary School fifth grade II cluster sub-district of Tanjung Raya.